Intolerance and Fear: A Critical Analysis of Cases of Religious Intolerance in Indonesia Based on a Study by Martha Nussbaum - Daniel M. Nainggolan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cases of religious intolerance in Indonesia are still quite high today. Government regulations on freedom of religion and laws that will ensnare perpetrators of intolerance seem incomplete to resolve the issue, so a more personal approach is needed to complete the process of handling cases of religious intolerance in Indonesia. Therefore, the purpose of this writing is to analyze and present additional dishes by borrowing Martha Nussbaum's menu in her book The New Religious Intolerance, using a qualitative method approach and collecting research data from books and journals, as well as other digital data related to the topic. The result, according to Nussbaum, is that religious intolerance arises because it is caused by a fear of others, therefore, offers three important offerings to solve the problem of religious intolerance. First, respect each other and build the principle of equality. Second, be self-aware and be fair. Third, respect for fellow human beings and foster a participatory and sympathetic imagination. These three combinations will be analyzed with the help of other supporting theories so that they can be presented as an effort to resolve religious intolerance in Indonesia.